Serovar distribution of a DNA sequence involved in the antigenic relationship between Leptospira and equine cornea - Arroyo Guillermo H; Parma Alberto E; Lucchesi Paula MA (BMC Microbiology, 2002)
Abstract Background Horses infected with Leptospira present several clinical disorders, one of them being recurrent uveitis. A common endpoint of equine recurrent uveitis is blindness. Serovar pomona has often been incriminated, although others have also been reported. An antigenic relationship between this bacterium and equine cornea has been described in previous studies. A leptospiral DNA fragment that encodes cross-reacting epitopes was previously cloned and expressed in Escherichia coli. Results A region of that DNA fragment was subcloned and sequenced. Samples of leptospiral DNA from several sources were analysed by PCR with two primer pairs designed to amplify that region. Reference strains from serovars canicola, icterohaemorrhagiae, pomona, pyrogenes, wolffi, bataviae, sentot, hebdomadis and hardjo rendered products of the expected sizes with both pairs of primers. The specific DNA region was also amplified from isolates from Argentina belonging to serogroups Canicola and Pomona. Both L. biflexa serovar patoc and L. borgpetersenii serovar tarassovi rendered a negative result. Conclusions The DNA sequence related to the antigen mimicry with equine cornea was not exclusively found in serovar pomona as it was also detected in several strains of Leptospira belonging to different serovars. The results obtained with L. biflexa serovar patoc strain Patoc I and L. borgpetersenii serovar tarassovi strain Perepelicin suggest that this sequence is not present in these strains, which belong to different genomospecies than those which gave positive results. This is an interesting finding since L. biflexa comprises nonpathogenic strains and serovar tarassovi has not been associated clinically with equine uveitis.